2010
DOI: 10.5657/kfas.2010.43.5.445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Lipid Sources on the Growth and Body Composition of the far Eastern Catfish, Silurus asotus

Abstract: This study investigated the effects of dietary lipid sources on growth performance and body composition of juvenile far eastern catfish, Silurus asotus. Three replicate groups of fish (average weight 3.6 g) were fed with one of the following experimental diets containing 10% beef tallow (BT), 5% BT plus 5% corn oil (CO), 5% BT plus 5% linseed oil (LO), or 5% BT plus 5% squid liver oil (SO) as the lipid source for 5 weeks. No significant difference was observed in the survival among groups. The weight gain of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…The fatty acid composition of fish in this study well reflected the fatty acid composition of dietary lipid. Similar results had been founded in previous catfish study ( Kim et al, 2010 ). Kim et al (2010) reported that linseed oil or squid liver oil containing n-3 fatty acids are the proper dietary lipid sources for the growth of juvenile far eastern catfish.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fatty acid composition of fish in this study well reflected the fatty acid composition of dietary lipid. Similar results had been founded in previous catfish study ( Kim et al, 2010 ). Kim et al (2010) reported that linseed oil or squid liver oil containing n-3 fatty acids are the proper dietary lipid sources for the growth of juvenile far eastern catfish.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, nutritional studies evaluating availability of dietary lipid source and substitution of fish meal with soybean meal for growth in this species have been performed ( Kim et al, 2009 ; 2010 ). However, information on growth performance of dietary protein and lipid levels is limited to date in this species.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental diets ( Table 1 ) were formulated as described by Kim et al [ 13 ] for this catfish species and 4-NP (CAS No. 104- 40-5, Sigma-Aldrich, >98%) was supplemented at 0.1 and 1.0 mg/kg diets.…”
Section: Methodsmentioning
confidence: 99%
“…Pellets were crumbled into particles, sieved to obtain appropriate sizes and stored at -70°C until fed. The control diet contained (in %): white fish meal 40, casein 13, beef tallow 5, corn oil 5, dextrin 27, α-cellulose 5.5, vitamin mix 2, mineral mix 2 and choline chloride 0.6 [ 13 ]. As the 4-NP content constituted a small portion of the diet, i.e., 0.01-0.1 mg/100 g diet in the 4-NP exposure groups, 4-NP was added to the control diet without further composition adjustments.…”
Section: Methodsmentioning
confidence: 99%
“…Kim et al, (2010) 16:0 (palmitic acid) 18:1n-9 (oleic acid, elaidic acid) n-3 HUFA , 16:0 18:1n-9 . , , sea bream, channel catfish, Atlantic halibut (Ibeas et al, 1996;Bae et al, 2004;Aksoy et al, 2009;Koizumi et al, 2009;Kikuchi et al, 2011).…”
mentioning
confidence: 99%